Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1093/qjmed/93.8.531
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, diagnosis and outcome of acute portal vein thrombosis

Abstract: The clinical features of acute portal vein thrombosis (APVT) are poorly defined in the literature. The proportion that progress to chronic PVT and the influences of various treatments are unknown. Between 1996 and 1998, nine patients presented to our hospital with varying upper gastrointestinal symptoms. They were found to have APVT by colour flow Doppler ultrasound, which was confirmed by CT scanning. All were tested for procoagulant tendencies and then treated with intravenous heparin for 7 days and warfarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 12 publications
2
79
0
9
Order By: Relevance
“…Sheen et al had shown a low HARI of 0.57 AE 0.11 in patients with portal vein thrombosis viz a viz a HARI of 0.75 AE 0.08 amongst controls. 4 Platt et al in a study of 35 patients with suspicious portal vein thrombosis showed a reduction in hepatic artery resistive index (HARI). He concluded from the study that reduction in HARI could be an objective parameter for portal vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheen et al had shown a low HARI of 0.57 AE 0.11 in patients with portal vein thrombosis viz a viz a HARI of 0.75 AE 0.08 amongst controls. 4 Platt et al in a study of 35 patients with suspicious portal vein thrombosis showed a reduction in hepatic artery resistive index (HARI). He concluded from the study that reduction in HARI could be an objective parameter for portal vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 While there are several studies that have reported portal vein and hepatic artery hemodynamics in healthy individuals 3 those with acute portal vein thrombosis, 4 therapeutic portal vein embolization, 5 and hepatic artery stenosis after liver transplant, 6 very few studies have looked into the portal hemodynamics in children with long standing extra hepatic portal vein obstruction (EHPVO). 7,8 Congestive index and venous pulsatility index in the portal vein, both in adult and pediatric patients are determinants of the hemodynamic status of the portal system.…”
mentioning
confidence: 99%
“…Sheen et al 9 demonstrated that 78% of noncirrhotic patients had resolution of their thrombus per CT reassessment after 3 months of oral anticoagulation with an INR range of 2 to 4. Condat et al 10 report in a retrospective study of acute PVT that recanalization occurred in 25 of 27 patients given anticoagulation and 0 of 2 patients without anticoagulation therapy.…”
Section: Treatment For Pvt With the Prothrombin Mutationmentioning
confidence: 99%
“…Nei casi di PVT senza infarto intestinale e a paziente emodinamicamente stabile, la terapia più frequentemente adottata e consigliata è quella che prevede l'uso dell'eparina sia non frazionata sia frazionata, seguita da terapia anticoagulante con warfarin [22][23][24][25][26][27] . La ricanalizzazione del circolo portale in questi casi viene descritta nel 50-80% dei pazienti a fronte di una totale assenza di ricanalizzazione nei pazienti non trattati.…”
Section: Quali Indagini Dovrebbero Essere Fatte Successivamente?unclassified